TEACHERSâ€™ BELIEFS ABOUT BULLYING, ANALYSIS TO REORIENT TEACHER TRAINING - PÃ©rez-Jorge, David; RodrÃguez-JimÃ©nez, MarÃa del Carmen; GonzÃ¡lez Contreras, Ana Isabel; Ruiz Ruiz, Jorge (Humanities & Social Sciences Reviews, 2020)
Purpose of the study: The objective of this study is to describe the beliefs, and opinions of the teachers of the Primary Education, Secondary Education, and Baccalaureate stages, regarding the phenomenon of bullying. Methodology: A random sampling procedure was used for the selection of participants. There were 224 teachers from Primary Education (32%), Secondary Education (56%), and the Baccalaureate (12%) who participated in a voluntary. The ages of the teaching staff were between 25 and 63 years. The majorities were women (87.4%) and half of the teachers reported bullied students in their classrooms. Main Findings: The results show that teachers are able to identify the most common bullying situations and consider that the cause is fundamentally socio-cultural. The teachers expressed a need for training in the field and those strategies for conflict management focus on dialogue and group and individual mentoring, and consider that preventive actions based on value education are highly desirable. Applications of this study: It can serve as a reflection to think about all the bullying situations that happen in any context and not only schools. Novelty/Originality of this study: the novelty of the study is that it analyzes the teachers’ beliefs about bullying in their centers, there are important errors about bullying that can influence detection and intervention in real situations of bullying.